DAMPAK PEMBAGIAN WAKTU KERJA TERHADAP FISIOLOGI, PSIKOSOSIAL, KINERJA, KESEHATAN, DAN KESELAMATAN KERJA DI PT. INDONESIA ETHANOL INDUSTRI - Farah Alhamid; Aan Rudiarto (Industrika : Jurnal Ilmiah Teknik Industri, 2017)
PT. Indonesia Ethanol Industry is one company that operates 24 hours, with the division of labor time in the morning, afternoon, and evening. The system implemented six working days within one week and get one day off. Working time sharing arrangements 1-3-2 pattern. That is two days early, two days nights, and two days late, then one day off. Over time, there are proposals for changes of employees through the management to try to change the division of labor time into a 3-2-1 pattern. Consideration of changes in the pattern so that the holiday is longer so that when you return to work can be more focused. The purpose of this study was to determine the distribution of effective working time seen from side physiology, psychosocial, performance, health and sfety in the PT. Indonesia Ethanol Industry at Jl. Cross East Coast KM 242 Village Sriwijaya District of Bandar Mataram Lampung Tengah. The method used in physiology and psychosocial research is Focus Group Discussion and to study the performance, health and safety using multiple correlation method. To make decisions based on the analysis method of variable ranking physiology, psychosocial, performance, health, and safety unknown variable is thehighest performance. The performance variables known at the time the division of labor pattern 3-2-1 the result of lower production compared with the distribution of working time pattern 1-3-2. Keywords: Distribution of Working Time, Physiology, Psychosocial, Performance, Health, and Work Safety.